Pengaruh Gaya Hidup dan Promosi Terhadap Kepuasan Konsumen EDC (Electronic Data Capture) Yokke yang Dimediasi Oleh Keputusan Pembelian” (Studi Kasus Pengguna EDC Yokke PT. Mitra Transaksi Indonesia) - Jhoni Hendra Sitepu; Hazmanan Khair; Fajar Pasaribu (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
The purpose of this study was to examine and analyze Lifestyle and Promotion of Consumer Satisfaction at EDC (Electronic Data Capture) Yokke which is mediated by consumer purchasing decisions directly or indirectly. The population in this study are all customers who use EDC Yokke. The sample in this study uses a sample of the slovin formula totaling 100 customers who use Electronic Data Capture. Data collection techniques in this study used documentation, observation, and questionnaire techniques. The data analysis technique in this study uses a quantitative approach using statistical analysis by using the Outer Model Analysis test, Inner Model Analysis, and Hypothesis Testing. Data processing in this study using the PLS (Partial Least Square) software program. The results of this study prove that directly lifestyle, promotion and purchasing decisions have a significant effect on consumer satisfaction, lifestyle and promotions have a significant effect on purchasing decisions, and indirectly purchasing decisions are able to mediate the influence of lifestyle and promotion on consumer satisfaction At EDC Yokke which means purchase decision acts as an intermediary variable..